Authentic Culinary Business for Sustainable Tourism: Strategy, Experience, Motivation and Value - Sri Mulyantini; Lidya Primta Surbakti; Agus Maulana; Ekawati Jati Wibawaningsih (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study analyzes the City Government’s strategy in developing culinary businesses to support sustainable tourism in Magelang (Central Java) and Depok (West Java), focusing on the role of natural resources, social dynamics, and cultural heritage. Methodology/approach: Using a qualitative case study approach, data were collected through unstructured interviews with 10 key informants from 2023 to 2024. The study examines government strategies and stakeholder involvement in preserving local identity and engaging tourists. Results/findings: Culinary business development emphasizes preserving cultural identity, providing training, and encouraging participation through exhibitions, cooking classes, and workshops. Storytelling and social media campaigns promote engagement. Sustainability is supported through legal protections, consistent promotion, and participation in festivals. Public education fosters cultural pride. The government integrates sustainable tourism principles by balancing economic, environmental, and social goals through collaboration with stakeholders. Concllusion: A strategic, culturally grounded, and collaborative approach is vital to developing sustainable culinary businesses and enhancing tourism appeal. Limitations: The study focuses on policymakers and business actors, excluding cultural stakeholders whose perspectives may offer additional insights. Contribution: The findings inform policy development to support culinary sustainability, encourage government-industry collaboration, and promote culture-driven culinary marketing for inclusive economic growth.